Marketing Dalam Manajemen Pendidikan Islam: Strategi Peningkatan Minat Masyarakat Terhadap Madrasah diMA Darussalam Kepahiang - Yanto, Ari; Wanto, Deri; Murniyanto, Murniyanto (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
Tight competition in the global era requires an educational institution to be as active as possible in marketing its institution to attract students' interest and gain public trust. This study aims to examine Marketing in Islamic Education Management related to the Strategy for Increasing Public Interest in Madrasas at MA Darussalam Kepahiang. This research is a qualiative research with a descriptive approach. Methods of data collection using the method of observation, interviews and documentation. Then the data is processed with the stages of analysis, reduction, presentation and drawing conclusions. The results show that the Strategy for Increasing Public Interest in Madrasahs at MA Darussalam Kepahiang is through collaborative collaboration and community approaches, quality development and improvement, leading trends and programs, marketing through digital media, proportional costs, and the application of good total quality management.